2020
DOI: 10.3390/rel11050241
|View full text |Cite
|
Sign up to set email alerts
|

Identity, Social Mobility, and Trauma: Post-Conflict Educational Realities for Survivors of the Rohingya Genocide

Abstract: The Rohingya refugee crisis is a humanitarian disaster with over 740,000 Rohingya leaving their homes in Rakhine State, Myanmar, since August 2017. In the process of this mass exodus, thousands have been brutally murdered and terrorized through a campaign of physical attacks by the Myanmar state including murder, beatings and mutilations; mass gang rape and sexual slavery of women and girls; and the burning of entire villages. The victims have been men, women, and children who were targeted because they belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…Likewise, while 20% of Bangladeshi adolescents were hungry in the four weeks prior to survey due to lack of food, this was true of 40% of Rohingya adolescents. Additional information on differences between Rohingya and Bangladeshi adolescents is detailed in a series of policy briefs published by the GAGE program ( Gender and Adolescence: Global Evidence (GAGE), 2020 ; Guglielmi et al., 2020 a; 2020 b; 2020 c; 2020 d; Bakali and Wasty, 2020 ). Keeping in mind the lower socioeconomic status of the Rohingya refugees even before the onset of the COVID-19 pandemic sets the stage for the burden of any negative impacts from the pandemic.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, while 20% of Bangladeshi adolescents were hungry in the four weeks prior to survey due to lack of food, this was true of 40% of Rohingya adolescents. Additional information on differences between Rohingya and Bangladeshi adolescents is detailed in a series of policy briefs published by the GAGE program ( Gender and Adolescence: Global Evidence (GAGE), 2020 ; Guglielmi et al., 2020 a; 2020 b; 2020 c; 2020 d; Bakali and Wasty, 2020 ). Keeping in mind the lower socioeconomic status of the Rohingya refugees even before the onset of the COVID-19 pandemic sets the stage for the burden of any negative impacts from the pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-COVID-19, Rohingya refugees were already suffering from insufficient essential services such as food, education, water and sanitation, and basic health care ( Banik et al., 2020 ; Islam and Nuzhath, 2018 ). For adolescents, the focus of this paper, previous mixed-methods research in Cox's Bazar found that Rohingya adolescent girls and boys are a particularly marginalised subpopulation that is failing to develop their full cognitive, emotional and social capabilities due to their precarious displacement status ( Gender and Adolescence: Global Evidence (GAGE) 2020 ; Guglielmi et al., 2020 a; 2020 b; 2020 c; 2020 d; Bakali and Wasty, 2020 ). Rohingya and Bangladeshi adolescents living in Cox's Bazar face a multitude of challenges, including age- and gender-based violence, disrupted educational prospects (particularly for older adolescents), widespread psychosocial distress and worry, and limited health service uptake ( Gender and Adolescence: Global Evidence (GAGE) 2020 ; Guglielmi et al., 2020 a; 2020 b; 2020 c; 2020 d; Bakali and Wasty, 2020 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the Rohingyas have been systematically denied access to fundamental social services such as education, health care, reproductive health, and the internet, effectively limiting them from access to critical information and aid from international humanitarian organizations (Khin 2017 ; Rosenthal 2019 ; Bakali and Wasty 2020 ). Before 2017, more than 70% of the Rohingya lacked access to safe water and sanitation services, and only 2% of Rohingya women gave birth in hospitals (Khin 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…7 Rohingya men, women and children were targeted because they belonged to a Muslim minority ethnic group that differed from the Burman Buddhist majority. 8 Furthermore, thousands of Rohingya were traumatised through physical attacks, sexual violence and the destruction of their homes. 9 The term ‘genocide’ will be used throughout this examination when describing the violence that began in August 2017.…”
Section: Introductionmentioning
confidence: 99%